Microlocal analysis of quasianalytic Gelfand-Shilov type ultradistributions. Issue 4 (2nd April 2016) - Cappiello, Marco; Schulz, René
Abstract : We introduce a global wave front set suitable for the analysis of tempered ultradistributions of quasi-analytic Gelfand–Shilov type. We study the transformation properties of the wave front set and use them to give microlocal existence results for pullbacks and products. We further study quasi-analytic microlocality for classes of localization and ultradifferential operators, and prove microellipticity for differential operators with polynomial coefficients.